Optimising infliximab induction dosing to achieve clinical remission in Chinese patients with Crohn’s disease - Zhu, Kouzhu; Ding, Xiaoliang; Xue, Ling; Liu, Linsheng; Wang, Yan; Li, Yun; Xi, Qinhua; Pang, Xueqin; Chen, Weichang; Miao, Liyan (Frontiers in Pharmacology, 2024)
Aims: A strategy based on therapeutic drug monitoring and population pharmacokinetic (popPK) models would likely increase the rate of clinical remission (CR) after infliximab (IFX) induction in patients with Crohn's disease (CD). This study aimed to evaluate the relationship between early IFX levels and antibodies to IFX (ATI) and CR at week 14 and simulate the probability of attaining the identified exposure target.Methods: Patients with CD (n = 140) treated with IFX were enrolled to develop the popPK model. Of these, 43 moderate-to-severe patients with CD were followed up at week 14. Simulations were performed on patients with different dosage regimens and covariates.Results: IFX levels >20.08 µg/mL at week 2, >18.44 µg/mL at week 6, and >3.08 μg/mL at week 14 were linked to CR. A one-compartment model fit the data best. The covariates influencing clearance were fat free mass, albumin and ATI levels. To achieve IFX levels > 20.08 µg/mL at week 2, ≥400 mg IFX was predicted to be required in over 50% patients with 45-70 kg and 35-45 g/L albumin, except for patients with 70 kg and 30 g/L albumin.Conclusions: IFX levels > 20.08 µg/mL at week 2 and absence of ATI at week 14 are associated with CR. Optimising IFX induction dosing will be critical to achieve the target of early IFX levels associated with CR.